Bicentric Synchronous Giant cell tumor: A Rare Managed Case Report of Bilateral Fibula Neck Tumor - Jogani, Abhinav (J Orthop Case Rep, 2020)
INTRODUCTION: Multicentric giant cell tumor (GCT) of bone is an uncommon variant of the typical solitary lesion, with numerous large series reporting an incidence of 0–1.4%. Multifocal lesions also appear to be more locally aggressive than their solitary counterparts and have higher rates of recurrence. Solitary GCT of proximal fibula usually involves fibular head, bicentric synchronous bilateral fibular neck involvement is a rare presentation. CASE PRESENTATION: An otherwise healthy 24-year-old boy presented with a palpable mass in the region of his left proximal fibula and B/L knee pain. He reported pain with activity but no peroneal nerve symptoms. Radiographs of his left knee revealed an expansile lytic lesion at the proximal fibula epimetaphyseal level while the right knee X-ray showed a similar smaller lesion. MRI was done to delineate the accurate extent of the tumor. On the left side, the patient underwent partial fibulectomy (en bloc resection) and chemical cauterization of the edges with 5% phenol. The other side GCT was smaller and the patient was largely asymptomatic, hence was planned for conservative management. CONCLUSION: Multicentric GCT is a known entity and diagnosis should be considered after thorough metabolic workup and after ruling out more common polyostotic skeletal lesions. Selected patients with aggressive (benign) and malignant tumors of the proximal fibula can be treated successfully by resection and with supplementary soft-tissue reconstruction, a good functional outcome can be anticipated.